(untitled) (Salam International Academic Journal, 2022)
As we know, words such as promise and contract are often mentioned as synonyms, and it is often thought that promise is the same as contract. In fact, it is hard for unprofessional persons to differentiate between these two mentioned concepts, but from the legal and professional point of views, there are many differences between these two terms. This research focuses on elaborating these differences from the point of view of Islamic Sharia and legal perspective. Actually, these two concepts are different in many ways such as in terms of the deadline, the obligation, the preface for the other, the parties and some other aspects. Thus, the differences between these two terms are studied in detail. The importance of this research lies in the fact that no research has been done on this topic yet in the national languages, and in Arabic language, the material about the topic is scattered and concise, and no special research has been done in this regard. In addition, it is very important subject since it is the need of people and these concepts are considered one of the daily affairs of current era. Our purpose from doing this research is to study the differences between promise and contract, and to know what concepts promise and contract represent. In this research, the usual methods, especially the library method are used. Finally, the research ends with discussion and conclusion, which will provide the reader with a better understanding of the subject.